Genetic structure of different ethnic populations at the frontotemporal dementia risk loci - Volodymyr Mavrych; Maryam Alamil; Olena Bolgova; Volodymyr Dvornyk (PLoS ONE, 2025)
Background and purpose Frontotemporal dementia (FTD) is a devastating neurodegenerative disorder affecting behavior, language, and cognition. It has a complex and still poorly understood genetic basis. The prevalence of FTD and other neurodegenerative disorders varies in populations of different ethnicities. This study aimed to analyze the genetic structure of different ethnic populations at FTD risk loci and provide insights into possible genetic factors underlying the above variation. Methods The data of single-nucleotide polymorphisms (in total 32) with genome-wide significance were extracted from the GWAS Database. The individual genotype data were retrieved from the 1000 Genomes Phase 3 Project. We analyzed several standard parameters of population genetic structure and computed a composite polygenic risk score. In total, five major ethnic superpopulations and 26 subpopulations were analyzed. Results All populations were significantly differentiated (P << 10−5) at the FTD risk loci. Ethnic populations manifested clear differences in the enrichment/depletion patterns of the risk alleles as evidenced by heatmaps. The population-specific unweighted genetic risk scores were relatively low and averaged at 0.091 ± 0.078. The scores differed significantly at the super- and subpopulation levels. Conclusions The results suggest that the major ethnic groups and their subpopulations differ by the allelic and genotypic structure at the FTD risk loci. This may be one of the key factors explaining the different prevalence of FTD across populations. However, currently available data on the epidemiology and genetics of FTD warrant further research.